2005
DOI: 10.1111/j.1365-2125.2005.02568.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of oxidative stress and modulation of autoantibodies against modified low‐density lipoprotein after rosuvastatin therapy

Abstract: AimsTo examine the effect of 24 weeks' rosuvastatin treatment on oxidative stress and changes in immune response to oxidized low-density lipoprotein (LDL). MethodsThis was an open-label study of patients in Austria receiving 10 or 40 mg rosuvastatin daily alternately during 12 and 24 weeks. Circulating concentrations of antibodies to malondialdehyde-oxidized LDL (MDA-LDL), both IgG and IgM type, to copper-oxidized LDL (Cu-OxLDL-IgG), concentrations of oxidized LDL complexed to IgG (OxLDL-IC) and markers of oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 52 publications
2
47
0
10
Order By: Relevance
“…The antioxidant capacity of sera was determined by a commercially available method (TAC ® -LDN, Nordhorn, Germany) as previously described (Resch et al 2006). The assay is based on the consumption of antioxidants present in the sample after the addition of hydrogen peroxide.…”
Section: Total Antioxidant Capacitymentioning
confidence: 99%
“…The antioxidant capacity of sera was determined by a commercially available method (TAC ® -LDN, Nordhorn, Germany) as previously described (Resch et al 2006). The assay is based on the consumption of antioxidants present in the sample after the addition of hydrogen peroxide.…”
Section: Total Antioxidant Capacitymentioning
confidence: 99%
“…In fact, titer of autoantibodies to ox-LDL was an independent predictor of the progression of carotid atherosclerosis in Finnish men [26]. In the previous studies, both rosuvastatin and fenofibrate have been associated with reduced ox-LDL levels [3,12,14,27]. Specifically, in a previous study, fenofibrate-associated ox-LDL reduction was greater in patients with high baseline ox-LDL levels, which was also the case in our study [14].…”
Section: Discussionmentioning
confidence: 52%
“…Clinical trials have reported that rosuvastatin reduces the levels of hs-CRP. hs-CRP is a marker which is closely associated with cardiovascular risk (33)(34)(35)(36)(37)(38)(39). Despite normal or low LDL cholesterol levels, rosuvastatin was shown to reduce hs-CRP and to reduce the production of other inflammatory markers, such as von Willebrand factor, fibrinogen, serum amyloid Aand platelet activating acetylhydrolase [37,40,41].…”
Section: Discussionmentioning
confidence: 99%